Increased plasma soluble thrombomodulin levels in cardioembolic stroke - Permphan Dharmasaroja (2018)
Soluble thrombomodulin (sTM) has been proposed as a potential marker of ischemic stroke. Results from previous studies remain controversial among different populations. We performed an analysis of plasma levels of sTM in Thai patients with acute ischemic stroke and determined whether sTM levels correlate with stroke subtypes, severity, and risk factors. Ninety-three patients and 76 controls were enrolled. Blood samples were obtained within 24 hours after stroke onset. Plasma sTM levels, measured using quantitative enzyme-linked immunosorbent assay, were significantly higher in patients than controls (P < .005), with the mean ±standard deviation (SD) levels of 3.08 ± 1.05 and 2.57 ± 1.15 ng/mL, respectively. Plasma levels of sTM in patients with cardioembolic subtype were significantly higher than in patients with other stroke subtypes, with the mean ± SD levels of 3.79 ± 1.26, 2.38 ± 0.68 (P < .009), and 2.38 ± 0.44 (P < .05) ng/mL for cardioembolism, large artery atherosclerosis, and small artery occlusion, respectively. Plasma sTM levels were not associated with stroke severity and risk factors of stroke; however, there was a slight relationship between high sTM levels and the presence of atrial fibrillation in the patient group. In conclusion, plasma sTM levels were increased in Thai patients with cardioembolic stroke and may be a potential marker during the acute phase. © 2012 The Author(s).